The Volcanic Landscapes of the Ancient Hunter-Gatherers of the Atacama Desert Through Their Lithic Remains - Loyola, Rodrigo; Figueroa, Valentina; Núñez, Lautaro; Vasquez, Marco; Espíndola, Christian; Valenzuela, Millarca; Prieto, Manuel (Frontiers in Earth Science, 2022)
Since ancient times Andean societies have formed an intimate relationship with volcanoes, the beginnings of which can be traced right back to the initial peopling of the region. By studying rocks used for stone tools and other everyday artifacts, we explore the volcanic landscapes of early hunter-gatherer groups (11,500 to 9500 cal BP) of the highlands of the Atacama Desert (22-23ºS / 67-68ºW). Petrological classification of the lithic assemblages of three Early Holocene archaeological sites showed the procurement of a great diversity of volcanic and subvolcanic rocks, including pumice, granitic rocks, micro-diorites, a large variety of tuffs and andesites, dacites, cherts, basalts, obsidians, among others. Field surveys enabled us to detect many of their sources related to volcanic features such as craters, maars, caldera-domes, lava flows, hydrothermal deposits, and ignimbrites. In these places, we also document large quarry-workshops and campsites from different periods, indicating intense and repeated human occupation over time. By comparing the artifacts with geological samples collected in the field, it was possible to establish lithic markers and assign the source of origin of a large part of the archaeological assemblages. Our data suggest that the volcanic features of the Atacama highlands were integrated into the mobility and interaction networks of ancient hunter-gatherer groups at an early date.